2014
DOI: 10.1177/0363546514529641
|View full text |Cite
|
Sign up to set email alerts
|

Second-Look Arthroscopic Evaluation of Cartilage Lesions After Mesenchymal Stem Cell Implantation in Osteoarthritic Knees

Abstract: The outcomes of MSC implantation for cartilage repair in OA knees seem encouraging; high BMI and large lesion size are important factors affecting outcomes. Although still in the early stages of application, MSC implantation for cartilage repair may have great potential for the treatment of OA knees. However, second-look arthroscopic findings revealed that 76% had the repair rated as abnormal or severely abnormal by ICRS standards. The development of an advanced surgical procedure with tissue-engineered scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 59 publications
8
133
0
Order By: Relevance
“…Four systematic reviews (35)(36)(37)(38) were also excluded. An assessment of the remaining 18 studies revealed that 10 used a single-arm prospective design (18)(19)(20)(39)(40)(41)(42)(43)(44)(45), four used quasi-experimental trials (46)(47)(48)(49) and four used RCT (50-53) (Table I). A total of 565 participants (226 males and 339 females) were included from the 18 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four systematic reviews (35)(36)(37)(38) were also excluded. An assessment of the remaining 18 studies revealed that 10 used a single-arm prospective design (18)(19)(20)(39)(40)(41)(42)(43)(44)(45), four used quasi-experimental trials (46)(47)(48)(49) and four used RCT (50-53) (Table I). A total of 565 participants (226 males and 339 females) were included from the 18 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…4 There have been multiple studies investigating the efficacy of stem cells in the treatment of both isolated cartilage lesions and osteoarthritis. 5 Pertinent to sports medicine, Koh et al 6 compared patients receiving microfracture surgery for cartilage defects of the knee with and without augmentation with adipose-derived stem cells. In a relatively small series, they demonstrated improved radiologic and subjective pain scores in the group receiving stem cell augmentation, although there was no difference in activity or quality of life.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Recent non-controlled clinical studies showed that local injections of ASCs improved clinical symptoms of pain and WOMAC index (i.e. a functional score), and reported that up to 100 millions of cells were well tolerated [54,55].…”
Section: Human Regenerative Therapy In Oamentioning
confidence: 99%